Imbabura and Chimborazo at the cradle of biogeography in the South American Andes (2020)
The biogeographic profiles produced between 1802 and 1803 by Alexander von Humboldt and Francisco José de Caldas can be postulated as synchronous, though dissimilar, infographics, centered respectively on two volcanoes in Ecuador: Imbabura and Chimborazo. This short article presents documentary and iconographic evidence to support this appreciation.